Application of Medical Professional Ethics in a Legal Context: Comparative Analysis of Ethical Cases and Legal Aspects - Haikal Mubarak; Hj. Yeti Kurniati; Hj. Hernawati RAS (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research explores the relationship between ethical values in medical practice and the governing legal framework, especially in the context of medical cases involving patient privacy and treatment decisions. Through an in-depth analysis of the differences and harmony between the principles of medical ethics and legal requirements, this research discusses the implications of these discrepancies for clinical decisions, physician responsibilities, and the protection of patient rights. These findings highlight the complexity of achieving appropriate alignment between the ethical values underlying medical practice and the legal framework governing medical practice